“.____________.” Taking Wittgenstein’s Prayers Seriously - Urszula Idziak-Smoczyńska (Religions, 2025)
This article examines Wittgenstein’s wartime private notebooks (MS 101–103), shifting attention from his philosophical reflections on religion and prayer to the abundance of written addresses to God found within the coded sections. Wittgenstein’s well-known assertion that “to pray means to think about the meaning of life” is juxtaposed with direct invocations of God and the Spirit, including the Pater Noster and prayers for courage and submission to the divine will. These invocations, accompanied by strokes or varied long em dashes framed by dots or exclamation marks which Martin Pilch has hypothesized to be symbolic representations of prayers—invite further reflection. Wittgenstein’s religious utterances are not merely outpourings of anguish, but manifestations of a sustained effort to align both life and work with the will of God, and to offer them for His glory. A compelling illustration of this spiritual orientation appears in M. O’C. Drury’s recollection of Wittgenstein’s declaration that his only wish was for his work to conform to the divine will. The interplay between philosophical inquiry and prayer evokes the Confessions of Saint Augustine, a spirit present throughout Wittgenstein’s work. Augustine’s integration of prayer and confession has similarly inspired 20th-century thinkers such as Jacques Derrida and Jean-François Lyotard. These Augustinian traces challenge conventional understandings of language and its limits, as well as the role of written language and punctuation, demanding a profound hermeneutics of the philosopher’s prayer.